All I want for Christmas is a trade agenda with teeth - Glauber, Joseph W. (American Enterprise Institute, 2023)
The past seven years have left the US trade agenda in shambles. In four short years, the Trump administration did its best to reverse a 75-year trend toward more open global markets—liberalization efforts previously led and championed by the United States. Within days of taking office, Donald Trump had pulled the US out of the Trans-Pacific Partnership and threatened to withdraw from the North American Free Trade Agreement and the US-Korea Free Trade Agreement. By the end of his four years, he had crippled the Dispute Settlement Body of the World Trade Organization (WTO) by refusing to appoint new members to its Appellate Body, imposed supplemental tariffs around the world on steel and aluminum imports, and plunged the US into a costly trade war with China.